Evaluating the role of a 99mTc-HYNIC-PSMA SPECT scan following a negative bone scan in men with prostate cancer: a single-centre, retrospective cohort study - Oppel, Cleve (Division of General Surgery, 2024)
Purpose: This study aimed to review the management of patients with high-risk and unfavourable intermediate-risk prostate cancer, who had a 99mTc-HYNIC-PSMA SPECT (technetium-99m hydrazine nicotinamide prostate-specific membrane antigen singlephoton emission computerised tomography) scan following a negative 99mTc-MDP (technetium-99m methylene diphosphonate) bone scan. Materials and methods: This study is a retrospective review of patients with high-risk and unfavourable intermediate-risk prostate cancer, who underwent a 99mTc-PSMA SPECT scan after a negative/equivocal bone scan between January 2018 and December 2020. Patients with a life expectancy of less than 10 years were excluded. Results: A total of 64 patients were investigated. The mean age was 63 years and the mean prostate-specific antigen (PSA) level was 40 ng/mL. The International Society of Urological Pathology (ISUP) scores were as follows: ISUP 1 in six patients, ISUP 2 in eight patients, ISUP 3 in 13 patients, and ISUP > 4 in 37 patients. A positive 99mTc-PSMA SPECT scan for disease metastases occurred in 20% of the patients who had a negative bone scan. Seven of the patients with a positive 99mTc-PSMA SPECT scan received a bilateral orchiectomy, while four patients received treatment with radical intent. Management of patients with both scans negative included external beam radiotherapy (EBRT) and androgen deprivation therapy (ADT) (n = 47), and radical prostatectomy with or without lymph node (LN) dissection (n = 4). A limiting factor was that not every patient underwent conventional cross-sectional imaging of the pelvis and prostate prior to intervention. Conclusion: A 99mTc-PSMA SPECT scan is a valuable diagnostic tool and was able to identify one in five men (20%) who are understaged by bone scan, allowing for their management plan to be tailored and sparing them morbid intervention.